Developments in Goat Semen Cryopreservations - Ranjan, R; Kumar, M; Gangwar, C; Kharche, SD (Animal Reproduction Update, 2022)
Sperm cryopreservation simplifies its storage for longer time for use in artificial insemination and assisted reproductive technologies. This technique is also important for breed conservation process and has paved the way for other reproductive biotechnologies. Despite the significant progress in the field, frozen-thawed sperm have enormous inconsistency in fertility rates. It is well known fact that semen cryopreservation exhibited detrimental effects on post-thaw semen motility, plasma membrane, acrosomal status and DNA integrity which ultimately effect the fertility outcome. In addition, several attributes are responsible for low quality of goat cryopreserved semen such as breeds, seasons, management practices and cryopreservation protocols. The aim of the review article is to give an insight of distant features of goat semen cryopreservation as well as recent development in goat semen cryopreservation. It also provides concise information on progress made in the advancement in the semen extender development and cryopreservation of goat sperm.